Ultra-sensitive protein detection with organic electrochemical transistors printed on plastic substrates. (25th July 2018) - Macchia, Eleonora; Romele, Paolo; Manoli, Kyriaki; Ghittorelli, Matteo; Magliulo, Maria; Kovács-Vajna, Zsolt M; Torricelli, Fabrizio; Torsi, Luisa
Abstract: The detection of protein biomarkers is of great importance in the early diagnosis of severe pathological states. Although in the last decade many approaches to achieve ultra-sensitive protein detection have been developed, most of them require complicated assay set-ups, hindering their adoption in point-of-care applications and on-spot diagnosis. Here we show an organic electrochemical transistor (OECT) biosensor printed on plastic substrates that can selectively detect Immunoglobulin G (IgG) with an unprecedented attomolar detection limit. The OECT is used as a transducer of the biorecognition event taking place at the gate electrode. The measured concentrations are well below the detectable limits of the leading clinical diagnostic enzyme-linked immunosorbent assay, and comparable to the ones gathered with the label-needing single molecule arrays platform. Our work benchmarks the role of plastic OECT-based biosensors as a powerful tool in simple, low cost, yet non-invasive, ultra-sensitive, and widely applicable immunoassay technology.